2018
DOI: 10.1002/2017jc013298
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Vertical Velocity Induced by Eddy Distortion in an Ocean Model

Abstract: Vertical motions within eddies play an important role in the exchange of properties and energy between the upper ocean and the ocean interior. Here we analyze alternating upward and downward cells in anticyclonic eddies in the East Australian Current region using a global eddy‐resolving model. The cells explain over 50% of the variance of vertical velocity within these eddies. We show that the upward and downward cells relate to eddy distortion, defined as the change in eddy shape over time. In anticyclonic ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…Meanwhile, we found that the near‐surface CHL concentrations are also influenced by the displacement of SCML, and they are enhanced (reduced) when SCMLs move upward (downward), regardless of eddy types and eddy locations (Figures b and c and Figure S5). Several modeling studies (e.g., Pilo et al, ; Zhang et al, ) suggest that vertical advection might be the dominant factor to induce displacement of seawater within eddies. Changes in stratification and relative vorticity in eddy interior constrained by conservation of potential vorticity, divergence of horizontal flow constrained by continuity, and eddy‐wind interaction‐induced Ekman pumping are very likely responsible.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, we found that the near‐surface CHL concentrations are also influenced by the displacement of SCML, and they are enhanced (reduced) when SCMLs move upward (downward), regardless of eddy types and eddy locations (Figures b and c and Figure S5). Several modeling studies (e.g., Pilo et al, ; Zhang et al, ) suggest that vertical advection might be the dominant factor to induce displacement of seawater within eddies. Changes in stratification and relative vorticity in eddy interior constrained by conservation of potential vorticity, divergence of horizontal flow constrained by continuity, and eddy‐wind interaction‐induced Ekman pumping are very likely responsible.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent numerical studies have reported that the dipole pattern of the vertical velocity arises in mesoscale eddies, similar to the patterns shown in Figures 8A,B, adiabatic up-and downwelling do not necessarily occur on the western and eastern side, respectively, of an anticyclone. Their orientation with respect to an eddy depends on how the eddy is detached from a main current (Pilo et al, 2018), and how the Q-vector distributes (Estrada-Allis et al, 2018). Before an anticyclonic ring is detached from the anticyclonic meander of the KE, the upwelling and the downwelling are seen from the meander trough to the crest, and from the crest to the trough, respectively (Bower and Rossby, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The eddies we examine are embedded within a dynamic mean flow, and among other mesoscale eddies with which they interact (Pilo et al, ). As a consequence, eddies are in constant change, and predictions of the time they retain water parcels from mean eddy characteristics (e.g., radius, vorticity, and depth extent) are not robust.…”
Section: Discussionmentioning
confidence: 99%